ANALISIS KEUNTUNGAN USAHA RUMAH PANGGUNG CV SIVEL DI DESA MOKOBANG KECAMATAN MODOINDING KABUPATEN MINAHASA SELATAN (Analysis of Business Profits of Stilt House Business of â€œCV Sivelâ€ s in Mokobang Village, Modoinding District, Minahasa Selatan Regency) - Rizal Josua Lembong; Leonardus Ricky Rengkung; Ribka M. Kumaat (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
This study aimed to analyze the profits of CV Sivel's